Secondary electron yield of emissive materials for large-area micro-channel plate detectors: surface composition and film thickness dependencies - Jokela, S. J.; Veryovkin, I. V.; Zinovev, A. V.; Elam, J. W.; Mane, A. U.; Peng, Q.; Insepov, Z. (Physics Procedia, 2012)
The ongoing development of Atomic Layer Deposition (ALD) enables the use of relatively inexpensive and robust borosilicate micro-channel substrates for use as Micro-Channel Plates (MCPs). The surfaces of the channels in these glass plates are functionalized to control the conductivity as well as the Secondary Electron Yield (SEY). The extensive SEY data found in literature show significant variation for a given material depending on the apparatus, the measurement procedure, and the sample preparation and handling. We present systematic studies on the effects of film thickness and surface chemical composition on SEY. We have modified an existing ultra-high vacuum apparatus containing X-ray and Ultraviolet Photoelectron Spectrometers (XPS and UPS, respectively) by adding a modified Low Energy Electron Diffraction (LEED) module for SEY measurements. With these tools, we have characterized the secondary electron emissive properties for MgO, Al2O3, and multilayered MgO/TiO2 structures to serve as electron emissive layers in the channels of the MCPs.
Keywords: Atomic Layer Deposition (ALD); Micro-Channel Plates (MCPs); Secondary Electron Yield (SEY)